Influenza AH1N1/09 en mujeres embarazadas: revisión de la literatura - Cabrera Fierro, Juan Sebastián; Suárez Ayala, Diana Vanessa; Gómez Cabrera, Fleider Leovani; Tejada Córdoba, Ángela Patricia; Chávez Dulce, Gerardo Rafael; Figueroa, Claudia Liliana (Universidad y Salud, 2011)
Most studies show that pregnant women are at increased risk for influenza. This risk is higher if you have an underlying medical condition, are elderly or have exposure in the third trimester. About the diagnostic tests, the RT- PCR has demonstrated be the most sensitive and specific for the detection of AH1N1/09 virus. Pregnancy should not be regarded as a contraindication for the use of drugs such as oseltamivir or zanamivir since the benefits of treatment outweigh the theoretical risks of the use of antivirals. No statistically significant differences in the use of oseltamivir against zanamivir. The aim of this article is to review the literature on the state of the art virus AH1N1/09 in pregnancy, diagnosis, treatment and prevention. A search in the databases MEDLINE and COCHRANE studies on Influenza AH1N1/09 in pregnancy.